2022
DOI: 10.1111/jzo.13007
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐scale vegetation complexity and habitat structure influence predation pressure on a declining snake

Abstract: In Western Europe, omnipresent human activities have considerable impacts on habitats at several spatial scales resulting in direct shifts in habitat characteristics. These modifications in habitat features can disrupt biotic interactions such as predation. Surprisingly, although snake species are facing a worldwide decline, relationships between habitat characteristics and predation pressure in snakes remain poorly understood. The main goal of this study was to assess predation pressure on a snake species (th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 95 publications
2
0
0
Order By: Relevance
“…Our study corroborates this by demonstrating that foxes were the dominant predator of lizards during the summer months in a semi‐arid region. More generally, our findings are consistent with previous studies of plasticine model reptiles that have found mammals to be dominant predators (Duchesne et al., 2022; Purger et al., 2017).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study corroborates this by demonstrating that foxes were the dominant predator of lizards during the summer months in a semi‐arid region. More generally, our findings are consistent with previous studies of plasticine model reptiles that have found mammals to be dominant predators (Duchesne et al., 2022; Purger et al., 2017).…”
Section: Discussionsupporting
confidence: 93%
“…(2022) observed that reptiles are more frequently found in the diets of foxes in areas with sparse vegetation and higher temperatures. This finding is complemented by other research underscoring the role of vegetation structure in moderating reptile predation risk (Duchesne et al., 2022; Hansen et al., 2019; Sato et al. 2014).…”
Section: Discussionsupporting
confidence: 65%